Enduring footprint of historical land tenure on modern land cover in eastern Mexico: implications for environmental services programmes. Issue 4 (20th October 2014) - Ponette‐González, Alexandra G; Fry, Matthew
<x xml:space="preserve">Abstract</x> Historical land‐tenure regimes and associated land‐use practices can have cumulative and persistent long‐term (centuries) effects on land cover in human‐modified landscapes. Thus, identifying areas historically preferred for specific land uses is important to prioritise sites for payments for environmental services (PES) programmes. We use historical studies spanning the 16th to 20th centuries, 1907 and 2007 land‐tenure maps, and a supervised classification of 2007 land cover to examine the footprint of historical land tenure on modern land cover in eastern Mexico. This information is then used to assess the conservation potential of forests and agroforests included in PES between 2003 and 2010. Our findings show that historical land tenure strongly influences the composition and spatial configuration of modern land cover in this region. In 2007, three land‐use and land‐cover types introduced by Spanish colonists and their heirs – grass/pasture, sugar cane and shade coffee – covered nearly three‐quarters of the study area. Moreover, the hacienda land‐tenure system stratified the landscape into well‐defined agroecological zones. In 2007, areas under hacienda control in 1907 had relatively more grass/pasture, sugar cane and urban, and relatively less forest and shade coffee land cover compared with areas not controlled by haciendas. Agricultural and urban lands were concentrated on gentle slopes and near roads, whereas forested lands were found on slopes >12 per cent and more distant from roads. Approximately 20 per cent of the land area targeted for PES fell within areas identified as historically preferred for intensive land use. Three to 25 per cent of the PES target areas were situated where forest and coffee would be expected to persist: on steeper slopes not previously controlled by haciendas and with low accessibility. By elucidating areas of relatively stable land cover as well as the responsiveness of different land‐cover types to underlying land‐use change drivers, our findings suggest that PES programmes could benefit from better understanding of landscape history.